ISSUES OF IDENTIFICATION OF NON-SMOKING TOBACCO PRODUCTS - T. A. Don; S. V. Kalashnikov; A. G. Mirgorodskaya (Новые технологии, 2020)
The consumer market for tobacco products is highly segmented by type of product, assortment, taste preferences of consumers and cost: these are traditional cigarettes, cigars, cigarillos, pipe and smoking tobacco, as well as  innovative products – various types of nonsmoking products – oral tobacco (sucking, chewing) and nasal (snuff).Traditional types of tobacco products are well studied, have clearly defined requirements formulated in government documents.Recently appeared in a large assortment of non-smoking tobacco products are positioned by manufacturers as a less toxic alternative to smoking tobacco and the possibility of painless smoking cessation.In this situation there is a need to reduce toxicity and to produce high quality products.Identification issues step forward, i.e. attribution of products to one form or another.In particular, the identification of non-smoking oral tobacco tobaccos, which have similar methods of consumption, component composition and differ only in individual technological methods, is very serious.The article deals with important and relevant issues of identification of non-smoking tobacco products and methods for determining technological indicators.As a result of the studies, the identification features of chewing tobacco have been established and draft methods for determining the fractional composition and humidity of chewing tobacco developed.